Challenges and Opportunities on Estrus Synchronization and Mass Artificial Insemination in Dairy Cows for Smallholders in Ethiopia. (28th May 2021) - Abebe, Belete; Alemayehu, Mulugeta
Abstract : In this paper, the potentials and constraints on estrus synchronization (ES) and artificial insemination (AI) practice for dairy cattle producers were overviewed. Compared to other African countries, Ethiopia has large numbers of dairy cattle population. However, the self-sufficiency in milk production is not yet attained due to the presence of a lot of limitations that hamper the success of ES and mass AI practice in many parts of the country such as improper selection of cows/heifers, inseminating a large number of cows/heifers in one day at a specific place (which creates stress for both AI technicians and female animals), absence of a data recording system, lack of clearly defined share of responsibilities among stakeholders, poor communication and collaboration among stakeholders, lack of motivations and skills of AI technicians, lack of support and readily available inputs, feed shortages, improper heat detection by smallholders and time of insemination, and lower reproductive performances of both indigenous and crossbred cows which consequently contributed to the unsuccessfulness of the technology.